LABOROTORY-CLINICAL- NEUROLOGICAL STATUS OF BILIRUBIN ENCEPHALOPATHY IN NEWBORN AND EARLY CHILDREN - M. A., Khushmurodova; Madjidova, Prof. Yo. N.; A, Abdiev (European Journal of Life Safety and Stability (2660-9630), 2021)
Jaundice is a common and often benign problem in neonates. In the first week of life around 60% of term neonates and 80% of preterm neonates develop jaundice. For yet unidentified reasons, bilirubin predominantly accumulates in the deep nuclei of the brain upon severe hyperbilirubinemia.